IDENTIFIKASI FAKTOR PENYEBAB OBESITAS PADA SISWA SEKOLAH DASAR NEGERI RANDUSARI - Feri Budi Setyawan (LPPM STKIP PGRI Sidoarjo, 2018)
The purpose of this research is to discuss about the obesity phenomenon which occurred in elementary school students of the country Randusari. This research aims to know the causes of obesity in elementary school students of the country Randusari. This research is quantitative descriptive research with engineering data retrieval using the test measurements of height and weight. The population in this research is the child in elementary school students of the country Randusari. Data analysis techniques using Descriptive Statistics Frequencies. The results of the research of the identification of external factors the causes of obesity in children is the relationship of genetic factors with the parents, not the share of food intake with energy output being consumed must be issued, and the lack of performing activities the sport has also become another cause factor against obesity it is art learning modules and skills at elementary school students of the country Randusari.